2000
DOI: 10.1111/j.1365-2621.2000.tb16019.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Various Dairy Proteins to Reduce Pink Color Development in Cooked Ground Turkey Breast

Abstract: Dairy proteins were evaluated for their ability to reduce pink color in ground turkey samples. Sodium nitrite and nicotinamide were added to induce pink color formation. Nonfat dry milk (NFDM) and 1 of the whey protein concentrates (WPC) reduced CIE a* values in samples containing 10 ppm sodium nitrite. All of the dairy proteins tested reduced CIE a* values in nicotinamide-treated samples. In samples prepared without nicotinamide or nitrite, only WPC reduced CIE a* values, while the other proteins tested had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Several investigations revealed the effects of non-meat ingredients in mitigating PCD in poultry products. These studies indicated that milk-derived ingredients (Table 8) such as non-fat dry milk (Dobson & Cornforth, 1992;Schwarz et al, 1997;Schwarz et al, 1999;Slesinski et al, 2000a), whey protein concentrate (Slesinski et al, 2000a;Sammel & Claus, 2003b), sodium caseinate (Slesinski et al, 2000a), and milk protein concentrate (Slesinski et al, 2000a) minimize PCD in poultry products. In addition, PCD can be decreased using common food-grade ingredients (Table 9) like citrate (Sammel & Claus, 2003a;Sammel, Claus, Greaser, & Richards, 2006;Kieffer, Claus, & Wang, 2000), calcium chloride , tricalcium phosphate , sodium tripolyphosphate (Young & Lyon, 1997),…”
Section: Cooked Color Phenomena In Poultrymentioning
confidence: 99%
“…Several investigations revealed the effects of non-meat ingredients in mitigating PCD in poultry products. These studies indicated that milk-derived ingredients (Table 8) such as non-fat dry milk (Dobson & Cornforth, 1992;Schwarz et al, 1997;Schwarz et al, 1999;Slesinski et al, 2000a), whey protein concentrate (Slesinski et al, 2000a;Sammel & Claus, 2003b), sodium caseinate (Slesinski et al, 2000a), and milk protein concentrate (Slesinski et al, 2000a) minimize PCD in poultry products. In addition, PCD can be decreased using common food-grade ingredients (Table 9) like citrate (Sammel & Claus, 2003a;Sammel, Claus, Greaser, & Richards, 2006;Kieffer, Claus, & Wang, 2000), calcium chloride , tricalcium phosphate , sodium tripolyphosphate (Young & Lyon, 1997),…”
Section: Cooked Color Phenomena In Poultrymentioning
confidence: 99%
“…The causes of undesirable pink color include high pH, high reducing conditions, the state and level of meat pigments, incidental nitrate/nitrite contamination, and processing ingredients ( Holownia et al , 2003 ; Maga, 1994 ). Many researchers investigated solutions to reduce pink color development by food ingredients ( Sammel and Claus, 2003 ; Sammel and Claus, 2006 ; Sammel and Claus, 2007 ; Schwarz et al , 1999 ; Slesinski et al , 2000 ). Slesinski et al (2000) observed that dairy proteins can reduce pink color in ground turkey breasts.…”
Section: Introductionmentioning
confidence: 99%
“…This allows a gel formation which provides some protection against heat denaturation during subsequent cooking and results in a more pink or red color. This can be counteracted by slight acidification with citric acid or by addition of certain dairy proteins (27). Negative aspects of these are the lessening of product yields by citric acid and the conflict with some religious requirements by combining meat and dairy proteins.…”
Section: Persistent Red Cooked Colormentioning
confidence: 98%